STRATEGI PENINGKATAN DAYA SAING PEDAGANG PAKAIAN PASAR MUNTILAN DENGAN METODE SWOT - Fatikha, Laila Nur (Transpublika Publisher, 2023)
Competition in the business world is increasing, the magnitude of the challenges and obstacles faced by business actors. Competition in the business world is getting tighter marked by the increasing variety of marketing strategies implemented to maintain its business. The purpose of this research was to analyze the marketing strategy applied by clothing traders in Muntilan Market, Magelang. This study uses the SWOT analysis method to help clothing traders in Muntilan Market increase their competitiveness so they can still compete with similar traders. This type of research uses descriptive qualitative, data collection by interview, observation and literature review. Based on the results of internal and external analysis, clothing traders are in an aggressive position (supporting the strategy). The right strategy is to optimize strengths and take advantage of opportunities.